I sistemi di monitoraggio a supporto delle attività nelle aree terremotate - Annamaria Giovagnoli; Nicole Dore; Antonio Monteleone (Archeomatica, 2018)
The "ArTeK Emergency" service intends to put itself in support of the institutions through the use of tools and techniques of the aerospace sector that feed the knowledge and accuracy of the information already available in Vincoli in Rete. The purpose of the service is to deliver the risks for the analysis of the post-emergency context for an objective support to the authorities involved in the management of safety activities and the safeguarding of cultural heritage.